Konseling Hukum dan Pendidikan Kesadaran Hukum bagi Siswa dalam Membangun Karakter Berorientasi Kewarganegaraan di SMP Al-Ihsan Mulia Medan - Dahris Siregar (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The goal of this legal counseling and education event is to make Al-Ihsan Mulia Junior High School Medan students more aware of the law and more civic-minded. Because they are young people, students need to know about legal, moral, and social duty so they can follow the rules at school and in the community. Students from classes XI-A and XI-B took part in this action through live lessons, quizzes, and group chats. The counseling materials stressed how important it is to follow school rules as a way to teach kids about the law from a young age and how this relates to learning about civics. The activity's results show that the students eagerly took part in the counseling, asked and answered questions, and understood how law, discipline, and building public character are connected. Students also showed that they had a better grasp on their responsibilities and rights as young citizens, as well as how important it is to follow the rules at school. Based on these results, we can say that this legal counseling and education practice works to make students more aware of the law and help them develop the values they need to be smart, good, and law-abiding young adults. By promoting legal knowledge from a young age in schools, this practice is meant to help keep people from breaking the law.